Comparison of Donepezil, Memantine, Melatonin, and Liuwei Dihuang Decoction on Behavioral and Immune Endocrine Responses of Aged Senescence-Accelerated Mouse Resistant 1 Mice - Zeng, Ju; Zhang, Xiaorui; Wang, Jianhui; Cheng, Xiaorui; Zhang, Yongxiang; Zhou, Wenxia (Frontiers in Pharmacology, 2020)
Ageing is a natural biological process associated with cognitive decline and neuroendocrine-immune changes, the neuroendocrine-immune system plays crucial role in brain ageing and neurodegeneration, it will be essential to discern beneficial attempts to delay ageing progress based on immunological ageing. In this study, we investigate the effects of Traditional Chinese medicines (TCMs) Liuwei Dihuang decoction (LW) and donepezil, memantine and melatonin on cognitive decline in ageing mice. The aged SAMR1 mice received oral administration of donepezil (1mg/kg), memantine (10 mg/kg), melatonin (10 mg/kg) and LW (10 g/kg) for 3 months, Shuttle box, Morris water maze and elevated-zero maze were performed to assess cognitive function, flowcytometry, Luminex and radioimmunoassary were measured the lymphocyte subsets, inflammatory factors and hormones. We observed that survival days of mice was increased with melatonin and LW, the anxiety behavior was significantly increased with memantine, melatonin and LW treatment, active avoidance responses significantly improved by LW, donepezil and memantine, the spatial learning ability was significantly improved by donepezil, and LW and melatonin have beneficial to spatial memory of old mice. For immune function, LW increased CD4+ and CD4+CD28+ cells and reduced TNF-α, IL-1β and G-CSF in plasma, promote the secretion of anti-inflammatory factors IL-4, IL-5 and IL-10 by regulating the active of Th2 cells in spleen. Donepezil and memantine exerts protective effect against CD4+CD28+ cells decrease caused by ageing and reduce the pro-inflammatory factor TNF-α, IL-1β and G-CSF in plasma, melatonin could reverse CD8+CD28+ cells imbalance and increased B cells. For endocrine factors, LW increased TSH level in pituitary, melatonin increased the GH level in blood. Our findings indicated that LW improve the cognitive decline in ageing mice might be associated with modulating the active T cells and HPG axis hormones, and increasing anti-inflammatory factors. Meanwhile, donepezil and memantine have advantages in regulating adaptive immunity, melatonin has advantages in the regulation of B cells and pituitary hormones, LW has better effect on neuroendocrine immune function compared with them from holistic view. LW might be a potential therapeutic strategy for anti-aging-related syndromes, and also provide a value on medication guidance about drug combination or treatment in clinical.